Wong Fook & Anor V Abdul Shukur Bin Abdul Halim (Wong Piang Loy, Third Party): A Seatbelt Prejudice - Hj. Talib, Norchaya (Journal of Malaysian and Comparative Law, 2019)
Wong Fook & Anor V Abdul Shukur Bin Abdul Halim (Wong Piang Loy, Third Party) – A Seatbelt Prejudice – Norchaya Hj. Talib